Representation of Tradition and Violence in Society in Shirley Jackson’s The Lottery - Az Zahra, Aisqa; Hasbi, Muh. (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study examines the representation of tradition and violence in Shirley Jackson’s short story, The Lottery, by utilizing Stuart Hall’s reception theory to analyze participants’ interpretations. It aims to understand how the readers of the story interpret these themes based on their personal experiences and cultural contexts. Employing a qualitative descriptive research design, data were collected through semi-structured interviews with five participants representing different background of ethnic groups, religions, and cultural tradition to reveal diverse perspectives on the normalization of violence under the guise of tradition. The data analysis was connected to Hall’s reception theory with three categories: dominant hegemonic, negotiated, and oppositional position. The findings indicate that one participant aligns with the dominant-hegemonic position, accepting traditional narratives without significant critique, while two participant adopts a negotiated position, recognizing the complexities of tradition yet grappling with its implications, and the other two participants are identified with oppositional position, indicating a critical stance towards traditional values and a rejection of their potential for harm. The result of this study provides more comprehensive perspectives toward the existence of violence in certain tradition and give a positive contribution to the analysis of cultural background of literary works.Keywords: Tradition, Violence, Recep[tion Theory, Social Norms, Ethics